Characterisation of local ikan pekasam and development of process for production of ikan pekasam from black pomfret (Parastromateus niger bloch) - Mohamad Azman, Ezzat (2014)
Ikan pekasam is a fermented fish product produced in Malaysia. It is usually made from freshwater fish, and the main source of carbohydrate for the fermentation process is ground roasted rice. In this study, the sensory and physicochemical properties including pH, titratable acidity, salt concentration, amino acids, biogenic amines, trans- and cisurocanic acid (UCA), and organic acids of 15 commercially available samples were determined. The samples comprised ikan pekasam made from two types of commonly used freshwater fish, namely lampam jawa (Puntius gonionotus) and black tilapia (Oreochromis mossambicus), that had undergone either natural or acid-assisted fermentation. Acid-assisted fermented samples are those that included either tamarind pulp (Tamarindus indica) or Garcinia atroviridis dried slices as an ingredient in the fermentation process. The result showed that there were significant differences (p ≤ 0.05) in pH values, total UCA (trans- plus cis-UCA) and cis-UCA contents between naturally and acid-assisted fermented ikan pekasam samples. However, there were many similarities including titratable acidity, salt concentration, biogenic amine contents namely histamine, tyramine, putrescine, cadaverine, 2-phenylethylamine, spermidine, and tryptamine. Other than that, there was also no difference in organic acid contents including for lactic, acetic, succinic, formic, malic, oxalic, citric, L-pyroglutamic, and fumaric acids between naturally and acid-assisted fermented ikan pekasam samples. However, there were significant differences (p ≤ 0.05) in amino acid contents namely leucine, isoleucine, valine, phenylamine, tyrosine, methionine and cysteine between naturally and acid-assisted fermented ikan pekasam samples. Garcinic and tartaric acids were detected in all samples fermented with added G. artroviridis slices and tamarind pulp, respectively. In general, biogenic amine, UCA, and organic acid contents varied greatly in both natural and acid-assisted fermented ikan pekasam samples. Sensory evaluation of the fifteen samples based on 9-hedonic scale indicated that there was no difference (p > 0.05) between natural and acid-assisted fermented ikan pekasam. Based on the sensory acceptability results of commercial ikan pekasam samples, ikan pekasam was then prepared from black pomfret (Parastromateus niger) using two separate processes used in natural and acid-assisted fermentation. In the first part, the fish were naturally fermented after they were mixed with 20% (w/w) salt for 3 days, washed after which equal proportion (w/w) of ground roasted rice and 10% (v/w) water were added to each batch and then mixed. For acid-assisted fermentation in the second part, black pomfret (P. niger) was mixed 100% salt (w/w). After salting for 1 week, 50% (w/w) of ground roasted rice, 3% (w/w) tamarind pulp, and 150% (v/w) water were added to each batch and also mixed. After mixing, all of batches were allowed to ferment for up to five weeks at ambient temperature for further analysis. According to the results of analysis, there were significant differences (p ≤ 0.05) in physicochemical properties between different fermentation periods in both fermentation processes (natural and acid-assisted). For examples, pH value was significantly lower (p ≤ 0.05) in five weeks fermented black pomfret compared to two and zero weeks fermented black pomfret. Other than that, biogenic amine, trans- and cis-UCA, and organic acid contents were significantly higher (p ≤ 0.05) in five weeks fermented black pomfret compared to two and zero weeks fermented black pomfret. Furthermore, there were only slight differences in physicochemical and sensory properties between ikan pekasam made from black pomfret, a marine fish, and ikan pekasam made from freshwater fish (black tilapia and lampam jawa). For example, there were significant differences (p ≤ 0.05) in total biogenic amine, total UCA (transplus cis-UCA), total organic acid including lactic, acetic, malic, and formic acids contents. However, there were many similarities between ikan pekasam from marine and freshwater fish including pH values, titratable acidity, salt content, and especially biogenic amine concentrations, namely histamine, tyramine, putrescine, cadaverine, 2- phenylethylamine, spermidine, and tryptamine. Based on the sensory evaluation using quantitative descriptive analysis (QDA), the intensity of attributes in two and five weeks naturally fermented black pomfret such as sourness odor, cohesiveness of fish flesh, sourness, saltiness, fishy, and fermented flavors were significantly higher (p ≤ 0.05) than two and five weeks acid-assisted fermented black pomfret, respectively. Furthermore, the panelists could detect significant (p ≤ 0.05) differences in five weeks naturally and acid-assisted fermented black pomfret samples, whereas the intensity of color, roughness of fish skin, sourness odor, sourness flavor, saltiness flavor, bitterness flavor, fishy flavor, fermented flavor, crispiness of fish skin, and oiliness texture increased as the fermentation time was increased. Also, there was no significant difference (p > 0.05) in overall acceptability scores between naturally and acid-assisted fermented ikan pekasam from freshwater fish (black tilapia and lampam jawa) and marine fish (black pomfret). It could be concluded that Malaysian traditional fermented freshwater fish (black tilapia and lampam jawa) and marine fish (black pomfret) can be consumed without any health risks. In general, there was no difference in most of the physicochemical and sensory properties between naturally and acid-assisted fermented fish even from different type of fish or fermentation process. However, there were significant differences (p ≤ 0.05) in physicochemical properties between different fermentation periods in naturally and acid-assisted fermented black pomfret, respectively.